THU0199 ABX464, A NOVEL DRUG IN THE FIELD OF INFLAMMATION, INCREASES MIR-124 AND MODULATES MACROPHAGES AND T-CELL FUNCTIONS. (2nd June 2020) - Begon-Pescia, C.; Mielle, J.; Campose, N.; Chebli, K.; Manchon, L.; Santo, J.; Apolit, C.; Martin, K.; Lapasset, L.; Vautrin, A.; Scherrer, D.; Garcel, A.; et al.
Abstract : Background: ABX464 is a small oral molecule with a novel mode of action. It binds the Cap Binding Complex, involved in the biogenesis of RNAs and predominantly upregulates the expression of a microRNA miR-124 in PBMCs and T cells (1). miR-124 has been widely described for its anti-inflammatory properties, with many confirmed targets i.e. monocyte chemoattractant protein 1 (MCP-1, CXCL-1, SERPIN-E1, STAT-3, IL-6 receptor. It post-transcriptionally regulates the expression of MCP-1 in rheumatoid arthritis (RA) synoviocytes and decreases their proliferation (2). While miR-124 is decreased in synoviocytes of RA patients, its injection in joint improved arthritis in rats (3). miR-124 expression in macrophages leads to the induction and maintenance of anti-inflammatory M2 phenotype (4). Its effect in T cells remains controversial. Objectives: (i) To assess the effect of ABX464 on miR-124 expression in vitro in macrophages and in vivo in patients; (ii) to assess the effect of ABX464 on arthritis in mice and (iii) to decipher the effect of ABX464 on human macrophages and T cells. Methods: miR-124 was measured in human monocyte-derived macrophages (huMDM) treated with ABX464 for 4 days and in patients with ulcerative colitis included in a phase IIa RCT in blood and rectal biopsies at day 56 by TaqMan qPCR. Collagen-induced arthritis (CIA) was induced using usual protocol and ABX464 was given by gavage 2 weeks at 40 mg/kg after the 2 nd injection of collagen and Freund adjuvant. HuMDM were exposed to 5 µM of ABX464 or DMSO (control) for 4 days, during a M1-polarization. Cytokines and chemokines were assessed in supernatants using both Proteome Profiler Array and Luminex. PBMCs were exposed to ABX464 (5 µM) for 6 days. Th1 (IFN-g+), Th17 (CCR6+IL-17+), Th2 (CRTH2+ IL-4+) and Tregs (CD25+CD125-/loFoxP3+) were assessed by flow cytometry. IL-6 receptor was assessed in CD4+ supernatant using ELISA. Results: ABX464 increased miR-124 in vitro by 3.41 folds in huMDM (p=0.001) compared to DMSO. The phase IIa RCT conducted in 32 patients with moderate to severe active ulcerative colitis showed a good safety profile and significant clinical efficacy. A strong increase of miR-124 was observed both in blood and rectal biopsies of patients treated with ABX464 (637 and 7.69 folds respectively, compared to placebo, p<0.05). The use of ABX464 drastically decreased the incidence of arthritis from 52% (15/ 29 mice) to 10% (3/30 mice) in a CIA model. Macrophages treated with ABX464 produced significantly less MCP-1 (median decrease -67%, p=0.004), CXCL-1 (-18%, p=0.004) and SERPIN-E1 (-53%, p=0.004), as confirmed by the two technics (n=9). ABX464 significantly decreased Th17 (-56%, p=0.02), while increasing Th2 (+21%, p=0.01). IL-6 soluble receptor was significantly decreased in supernatant of PBMCs treated with ABX464 (-43%, p=0.04). Conclusion: We demonstrated that ABX464 increases miR-124 both in vitro and in ulcerative colitis patients. In vitro, ABX464 decreased the expression of miR-124 target genes, that is MCP-1, CXCL-1, SERPIN-E1 in macrophages and decreases the number of Th17 as well as IL-6 soluble receptor in CD4+ T cells. A phase IIa RCT is currently ongoing in patients with rheumatoid arthritis and inadequate response to methotrexate and/or TNF-inhibitors (n=60). Results are expected during 2020 summer. References: [1]Vautrin A et al. Sci Rep. 2019;9:792 [2]Nakamachi Y et al. Arthritis Rheum 2009; 60:1294-304 [3]Nakamachi Y et al. Ann Rheum Dis 2016; 75:601-8 [4]Veremeyko T et al. PLoS ONE 2013; 8:e81774 Disclosure of Interests: Christina BEGON-PESCIA: None declared, Julie Mielle: None declared, Noélie Campose Employee of: ABIVAX, Karim Chebli Consultant of: ABIVAX, Laurent Manchon: None declared, Julien Santo Employee of: ABIVAX, Cécile Apolit Employee of: ABIVAX, Kévin Martin Grant/research support from: ABIVAX, Laure Lapasset Employee of: ABIVAX, Audrey Vautrin Employee of: ABIVAX, Didier Scherrer Employee of: ABIVAX, Aude Garcel Employee of: ABIVAX, Jamal Tazi Shareholder of: ABIVAX, Grant/research support from: ABIVAX, Consultant of: ABIVAX, Employee of: ABIVAX, Paid instructor for: ABIVAX, Speakers bureau: ABIVAX, Claire DAIEN Grant/research support from: from Pfizer, Abbvie, Roche-Chugaï, Novartis, Abivax, Sandoz, Consultant of: Abbvie, Abivax, BMS, MSD, Roche-Chugaï, Lilly, Novartis, Speakers bureau: Abbvie, Abivax, BMS, MSD, Roche-Chugaï, Lilly, Novartis